STUDY ON ART AND ARCHITECTURAL PATTERN OF THE SUN TEMPLE OF KONARK IN EASTERN INDIA - Mohapatra, Ratnakar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
The aim of article is to emphasize the arts and architectural features of the Sun temple of Konark in the Puri district of Odisha. This massive Sun temple, constructed in the traditional Kalinga style, is shaped like a chariot of the Sun God, drawn by a group of seven horses and equipped with twelve pairs of exquisitely engraved stone wheels. Because of the temple's stunning eastward slope, the main entrance is first struck by the first light of dawn. An elephant and a man are crushed beneath the two enormous lions guarding the entrance on either side. The outside walls of the temple are covered in carvings of erotica, beasts, monsters, warriors, and animals. The enormous, seventy-meter-tall main sanctum, known as Vimana, collapsed in 1837 as a result of the heavy structure and poor soil. Around the main temple, archaeologists have also uncovered a few other subsidiary temples of the eleventh-century. The Mayadevi temple honors one of the wives of the Sun God, while the other is thought to be devoted to Lord Vishnu. There are a good number of "Mithuna" sculptures at Konark Sun temple. Aside from the entrance, the only remaining buildings today are the "jagamohana" (porch) and "Nata Mandir" (Dancing Hall). The Nata Mandir alludes to the 'Devdasis' tradition, in which dancers resided within the temple complex and dedicated their lives to classical dances such as Bharatnatyam and Odissi. The third point in the state's golden triangle is Konark Sun Temple; the first two points are Jagannath Puri Temple and Bhubaneswar Lingaraj Temple. It was originally constructed on the sea bank by Narasimhadeva-I, but it is now quite a distance from the coast. Just outside the Sun temple is the Nine Planets Temple, also known as the Navagraha Temple. Inside is a massive black slab that has idols of the nine planets carved out of chlorite stones. Originally housed above the main doorway, the slab is currently on display within the Navagraha temple. Out of three structures of Sun temple, the structure of jagamohana is only survived till today, but some portions of the vimana and natamandapa portions have existed to know their designs and plans.